Analisis Pengaruh Kepuasan Pelanggan Terhadap Minat Beli Kembali Di Aplikasi Shopee Serta Dampaknya Pada Keunggulan Bersaing - Fredy Olimsar; Feny Tialonawarmi (Journal of Economic, Bussines and Accounting (COSTING), 2023)
In general, people today do a lot of buying and selling online through e-commerce because there is no need to go to a shopping center and transactions can be done easily and quickly. Various kinds that can be done in this online business, one of them by using an application. The most popular online shopping platform applications in Indonesia are Shopee, Lazada, Tokopedia, Bukalapak, Blibli. One of the objectives of this study is to identify and analyze the effect of customer satisfaction on competitive advantage through repurchase interest as a mediating variable. The results of this study indicate that there is an influence of customer satisfaction on competitive advantage mediated by repurchase interest. This means that when customers feel like making repeat purchases, customers are satisfied with the Shopee application they use and can be superior if many customers make repeat purchases. On the other hand, if the online shopping platform ignores customer satisfaction and creates customer dissatisfaction, it will affect the repurchase intention of its customers, which will have a negative impact on competitive advantage. Keywords: Customer Satisfaction, Repurchase Intention, Competitive Advantage, Shopee Application